Analytical Study of Breaststroke Technique Based on Movement Phases in Bumi Phala Swimming Athletes - Robertus Dafa Tiara Talitakum Mardian; Fajar Awang Irawan (STKIP Taman Siswa Bima, 2026)
Breaststroke requires precise coordination across distinct movement phases to achieve optimal propulsion and efficiency. This study aimed to analyze breaststroke technique based on movement phases among athletes of the Bumi Phala Swimming Team, Temanggung. A descriptive quantitative design was applied involving 20 athletes selected through purposive sampling. Data were obtained using underwater video recordings from front, side, and rear perspectives and analyzed through frame-by-frame motion analysis using Kinovea software (version 0.9.5). The analysis focused on the glide phase, arm pull (outsweep–insweep), breathing, recovery and leg kick, and arm–leg coordination. The results showed that overall technique was classified as fairly good, with the highest conformity observed in the arm pull and breathing phases. In contrast, inconsistencies were identified in the glide and leg kick phases, indicating reduced movement efficiency. These findings highlight the need for phase-specific technical evaluation to support targeted coaching interventions, particularly to optimize glide and kicking mechanics for improved breaststroke performance.